Babad Stories: Balinese Narratives recreated on the scene (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The narratives of the balinese topeng dance-drama depict historical and mythological chronicles of the times when Bali was under the influence of the Majapahit empire (1293-1520) and during the migration of the javanese court to the island. They report the daily life and the great deeds of the ancient balinese and javanese kings as well as their relations with the aristocracy, the foundations of villages and the development of genealogies. But what narratives would these be and how do balinese artists transport their history and myths to the dramatic scene? This study brings up four babad chronicles and analyzes the transposition of one of them to the performance moment as an example.
Keywords: Babad; Bali; Topeng; Dance-drama; Mask